Microalgal-bacterial granular sludge for municipal wastewater treatment: from concept to practice - Zhang, Xiaoyuan (2022)
Recently, increasing interest has been placed in microalgal-bacterial granular sludge (MBGS) in the journey towards the energy and carbon neutrality of municipal wastewater treatment. Different from aerobic granular sludge, the performance of MBGS is mainly determined by the mutualism and symbiosis between coexisting microalgae and bacteria. It appears from the literature that most of studies on MBGS were conducted at small benchtop scales under controlled conditions with synthetic wastewater. Therefore, this article attempts to look into the major engineering gaps between the knowledge generated from numerous laboratory research works and the large-scale application of MBGS, including massive production of MBGS, type of bioreactor, effect of alternate photo and dark metabolisms on effluent quality, resource recovery from waste MBGS, etc. It is clearly demonstrated that MBGS is still at its infant stage, and more effort is strongly needed to identify the technological bottlenecks of full-scale applications, while providing corresponding engineering solutions.